Validation of Sonography findings of synovitis and tenosynovitis of hands and wrists in patients with systemic sclerosis. Issue 3 (October 2018) - Scheiman-Elazary, Anat; Ranganath, Veena K; Ben-Artzi, Ami; Kafaja, Suzanne; Borazan, Nabeel H; Woodworth, Thasia; Duan, Lewei; Elashoff, David; Clements, Philip; Furst, Daniel E
Objectives: Validating musculoskeletal ultrasound features of the joints and tendons of the hands in a large scleroderma cohort. Methods: A total of 81 scleroderma patients participated in this prospective, cross-sectional study. Grayscale and power Doppler musculoskeletal ultrasound images of 13 joints and 5 tendons of the wrist and hand were obtained. Clinical assessment included modified Rodnan skin thickness score, joint count, and Scleroderma Health Assessment Questionnaire. Face validity, content validity, construct validity, and feasibility were assessed. Results: Mean age was 53.8 years (range 22–80), 76.5% were females, and disease duration ranged from 0.25 to 29 years. Mean length of the examination was 36 min. Scleroderma Health Assessment Questionnaire–Disability Index correlated with musculoskeletal ultrasound erosions (r = 0.5, p = 0.0003). Skin score correlated with tendinitis grayscale (r = 0.26, p = 0.02). Intra-reader correlation coefficient for musculoskeletal ultrasound was 0.96 for the joints and could not be calculated for tendons because there were too few positive findings. When tendon changes existed, percent of agreement was 77.7%–83.3%. Conclusion: Musculoskeletal ultrasound of 13 joints and 5 tendons of the hands and wrist has face and content validity. Construct validity was shown for the tendons and erosion scores. Feasibility and reliability were partially validated.